The challenges of stem cell research in Nigeria - Agbedia, Clara Oniovokoyubu; Oshegbo, Godwin Efe (International Journal of Advanced Nursing Studies, 2013)
Many patients and their families, have great expectations that Stem cell therapy could be the cure for a host of devastating diseases such as Parkinson's disease, Alzheimer's dementia, diabetes, multiple sclerosis, burns, etc. As stem cell research gains ground in Nigeria, it is appropriate to explore the issues surrounding the use of human embryos for stem cell research and its implication from a nursing perspective. In this paper the socio-political implications of the use of embryonic stem cell research was addressed. The nursing, medical and legal literature (both print and electronic) related to Stem cell research and therapy were evaluated and the main ethical issues raised by the destruction of human embryos were examined.  There must be a public discussion/debate on the benefits including its cost implication. Nigerians must evaluate the appropriateness of stem cell technologies within their own national contexts and prioritize which applications are the most promising for improving their health.